Paramagnetic magnetization signals and curious metastable behaviour in field-cooled magnetization of a single crystal of superconductor 2H-NbSe2. (29th July 2015) - Kumar, Santosh; Tomy, C V; Balakrishnan, G; Paul, D McK; Grover, A K
Abstract We present here some newer characteristics pertaining to paramagnetic Meissner effect like response in a single crystal of the low <?CDATA ${T_{\text{c}}}$ ?> <?MML Tc ?><inline-graphic xlink:href="ark:/27927/pgj2c93hv18" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> superconducting compound 2H- <?CDATA $\text{NbS}{{\text{e}}_{2}}$ ?> <?MML NbSe2 ?><inline-graphic xlink:href="ark:/27927/pgj2c93hqsb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> via a detailed study of effects of perturbation on the field-cooled magnetization response. In the temperature range, where an anomalous paramagnetic magnetization occurs, the field-cooled magnetization response is found to be highly metastable: it displays a curious tendency to switch randomly from a given paramagnetic value to a diamagnetic or to a different paramagnetic value, when the system is perturbed by an impulse of an externally applied ac magnetic field. The new facets revealed in a single crystal of 2H- <?CDATA $\text{NbS}{{\text{e}}_{2}}$ ?> <?MML NbSe2 ?><inline-graphic xlink:href="ark:/27927/pgj2c93htj1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> surprisingly bear a marked resemblance with the characteristics of magnetization behaviour anticipated for the giant vortex states with multiple flux quanta ( <?CDATA $L{Φ_{0}}$ ?> <?MML LΦ0 ?><inline-graphic xlink:href="ark:/27927/pgj2c93hrzm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, <?CDATA ${Φ_{0}}=hc/2e$ ?> <?MML Φ0=hc/2e ?><inline-graphic xlink:href="ark:/27927/pgj2c93ht29" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, <?CDATA $L>1$ ?> <?MML L>1 ?><inline-graphic xlink:href="ark:/27927/pgj2c93hvtz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) predicted to occur in mesoscopic-sized superconducting specimen and possible transitions amongst such states.